Reliability- and cost-based redundancy design for modular multilevel converter - Tu, Pengfei (2020)
The modular multilevel converter (MMC) is very attractive in a high-voltage dc (HVdc) transmission system due to its high modularity and scalability. It is also a promising candidate for medium-voltage applications. An MMC has many power devices that lead to a relatively low reliability based only on a direct failure rate calculation. The reliability of an MMC can be improved by redundant designs. Lots of redundant designs and strategies have been proposed in recent years, while their reliability improvements are hardly quantified in existing literature. In practice, reliability improvement with constraint costs is a challenge. In view of these, this paper proposes a reliability and cost assessment scheme for MMC redundant designs and strategies. Reliability and cost are quantified for comparison purposes. A medium-voltage application is used to demonstrate the reliability and cost assessment scheme. The reliability analysis is based on a combinatorial model and the Poisson process model. The cost analysis focuses on capital cost and power loss cost. The proposed reliability and cost analysis scheme provides a guideline for MMC redundant design and redundant strategy selection.